Nationalizing same-sex marriage: assessing the effect of Baehr v. Lewin on the Federal Defense of Marriage Act - Perez, Melissa L., author; Daum, Courtenay, advisor; Velasco, Marcela, committee member; DeMirjyn, Maricela, committee member (Colorado State University. Libraries, 2011)
Since the Defense of Marriage Act, the issue of same-sex marriage has dominated the political discourse of lesbian, gay, bisexual, and transgender politics. Scholars claim that the litigation in Hawaii that took place in the 1990s was responsible for the subsequent political activity surrounding same-sex marriage in the United States, including the Defense of Marriage Act, but none has empirically tested this claim. This paper seeks to understand whether or not the litigation in Hawaii prompted congressional action that resulted in the introduction of the federal Defense of Marriage Act and if so, why. By using Kingdon's multiple streams framework as a guiding tool, this research evaluated different political participants and factors to understand how the litigation in Baehr v. Lewin (74 Haw. 530; 852 P.2d 44; 1993) connects to the federal Defense of Marriage Act. This paper finds that the litigation in Hawaii is the catalyst that prompted the subsequent activity that resulted in the Defense of Marriage Act by energizing a well organized coalition opposed to same-sex marriage to expand the political debate and move the issue of same-sex marriage from the state courts in Hawaii to Congress.
Keywords: Defense of Marriage Act; same-sex marriage; Hawaii; gay marriage